Editorial: Dynamics in agricultural value chains - Dannenberg, Peter; Kulke, Elmar (DIE ERDE – Journal of the Geographical Society of Berlin, 2014)
This editorial gives a brief overview on current approaches on value chains and production networks in general and, more specifically, in the field of agriculture. Based on this background it is outlined where the authors see new conceptual and applied perspectives for research in these areas. The individual articles of the special issue are introduced and it is discussed in how far the papers of this special issue can contribute to the aforementioned new research perspectives.